Energy efficiency analysis of antenna selection multi‐input multi‐output automatic repeat request systems over Nakagami‐m fading channels. Issue 12 (1st August 2015) - Le, Ngoc Phuc; Tran, Le Chung; Safaei, Farzad; Varma, Vineeth Satheeskumar
Abstract : In this study, the authors investigate energy efficiency in antenna selection multi‐input multi‐output automatic repeat request (MIMO ARQ) wireless systems. The authors first derive an approximate expression for the average frame‐error rate (FER) in antenna selection MIMO systems over quasi‐static Nakagami‐ m fading channels. The FER approximation is then used to obtain an analytical expression of an energy‐efficiency metric that is defined as the total energy required to successfully deliver one information bit. The authors prove that this energy‐efficiency metric is a quasi‐convex function with respect to the average signal‐to‐noise ratio value. Based on this analysis, the authors obtain the optimal value of the average energy per transmitted data symbol such that the total energy consumption in the system is minimised. The results show that the energy efficiency in antenna selection MIMO ARQ systems is improved when the number of equipped antennas is increased. Simulation results are provided to validate the analysis.